Lokus Kecerdasan Spiritual dalam Perspektif Al-Qur’an Kajian Tematik atas Peran Sentra Qalbu - Iskandar, Iskandar (Lajnah Pentashihan Mushaf Al-Qur'an, 2012)
One of the most precious aspects of all human potential is intelligence. Intel-ligence, whichÃ‚Â arises fromÃ‚Â the human brain, has been able to bring people to advanced stages of civilization.Ã‚Â However, these advancements cannot always be enjoyed by modern society as there are those who continue toÃ‚Â experience alienation and isolation. This fact has encouraged the emergence of a concept of intelligence which is based on spiritual, and not merely intellectual strength.Ã‚Â It is popularly calledÃ‚Â Ã¢â‚¬Ëœthe spiritual intelligenceÃ¢â‚¬â„¢. This articleÃ‚Â utilises a thematic interpretative approach to explain how the Qur'an views the concept of intelligence as poessessed by individuals.